Women’s involvement in medical decision-making during pregnancy and childbirth - Dios, Angelina (2022)
Objective: Promoting women’s participation during pregnancy and childbirth is in line with the call of the World Health Organization and is associated to effects on user satisfaction, clinical health outcomes and better management of health care providers. Objective: To discover the women´s need for participation in decision making during pregnancy and childbirth. Methods: Secondary analysis of a descriptive qualitative study conducted with hospitalized women from the puerperium service of two public hospitals in Santiago, Chile. Data analysis was performed using the method proposed by Grounded Theory. Results: Twelve women participated in two focus groups. From the relational analysis it is clear that participation in the reproductive process is interfered by two groups of factors linked to cultural meanings and to the violation of women’s rights. Conclusions: Women’s participation in clinical decisions during pregnancy and childbirth is still scarce and power is still held by health professionals, perpetuating practices of institutional violence. To advance in obstetric practice centered on women, it is important to recognize the active role that women want and can play to have a positive and satisfactory experience.